Sex differences in diabetes and risk of incident coronary artery disease in healthy young and middle-aged adults - Kalyani, Rita Rastogi; Lazo, Mariana; Ouyang, Pamela; Turkbey, Evrim; Chevalier, Karinne; Brancati, Frederick; Becker, Diane; Vaidya, Dhananjay (Diabetes care, 2014)
Controversy exists about the coronary artery disease (CAD) risk conveyed by diabetes in young and middle-aged women. We investigated sex differences in CAD by diabetes status among healthy individuals with different underlying risks of heart disease. We examined subjects aged <60 years without CAD at enrollment in the high-risk GeneSTAR Study (n = 1,448; follow-up ∼12 years), Multi-Ethnic Study of Atherosclerosis (MESA; n = 3,072; follow-up ∼7 years), and National Health and Nutrition Examination Survey III (NHANES III) Mortality Follow-up Study (n = 6,997; follow-up ∼15 years). Diabetes was defined by report, hypoglycemic use, and/or fasting glucose ≥126 mg/dL. The outcome was any CAD event during follow-up (fatal CAD in NHANES). In the absence of diabetes, CAD rates were lower among women in GeneSTAR, MESA, and NHANES (4.27, 1.66, and 0.40/1,000 person-years, respectively) versus men (11.22, 5.64, and 0.88/1,000 person-years); log-rank P < 0.001 (GeneSTAR/MESA) and P = 0.07 (NHANES). In the presence of diabetes, CAD event rates were similar among women (17.65, 7.34, and 2.37/1,000 person-years) versus men (12.86, 9.71, and 1.83/1,000 person-years); all log-rank P values > 0.05. Adjusting for demographics, diabetes was associated with a significant four- to fivefold higher CAD rate among women in each cohort, without differences in men. In meta-analyses of three cohorts, additionally adjusted for BMI, smoking, hypertension, HDL, and non-HDL cholesterol, antihypertensive and cholesterol-lowering medication use, the hazard ratio of CAD in men versus women among nondiabetes was 2.43 (1.76-3.35) and diabetes was 0.89 (0.43-1.83); P = 0.013 interaction by diabetes status. Though young and middle-aged women are less likely to develop CAD in the absence of diabetes, the presence of diabetes equalizes the risk by sex. Our findings support aggressive CAD prevention strategies in women with diabetes and at similar levels to those that exist in men.